2011
DOI: 10.1021/ja208827q
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Proficiency: The Extreme Case of S–O Cleaving Sulfatases

Abstract: As benchmarks for judging the catalytic power of sulfate monoesterases, we sought to determine the rates of spontaneous hydrolysis of unactivated alkyl sulfate monoesters by S-O bond cleavage. Neopentyl sulfate proved to be unsuitable for this purpose, since it was found to undergo hydrolysis by a C-O bond cleaving mechanism with rearrangement of its carbon skeleton. Instead, we examined the temperature dependence of the spontaneous hydrolyses of aryl sulfate monoesters, which proceed by S-O cleavage. Extrapol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
146
0
5

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(162 citation statements)
references
References 34 publications
11
146
0
5
Order By: Relevance
“…Luo et al 2012a). This is doubly important in light of the fact that sulfates fulfill many of the same biological functions as phosphates ; however, it seems to appear that they are even more inert than phosphate esters in aqueous solution (it has been suggested that S-O cleaving enzymes as the most proficient known to date, Edwards et al 2012), and, the requirement of an ' external' base makes it more challenging to evolve for sulfatase activity than for phosphatase activity, which perhaps explains the prevalence of phosphate over sulfate esters in biology. Despite this, however, it is the same multitude of potential pathways that makes phosphate esters so versatile to catalyze also so difficult to study, and there are a large number of open questions remaining in the field, which need urgent addressing in light of the biological importance of phosphates.…”
Section: Why Nature Really Used Phosphatementioning
confidence: 99%
“…Luo et al 2012a). This is doubly important in light of the fact that sulfates fulfill many of the same biological functions as phosphates ; however, it seems to appear that they are even more inert than phosphate esters in aqueous solution (it has been suggested that S-O cleaving enzymes as the most proficient known to date, Edwards et al 2012), and, the requirement of an ' external' base makes it more challenging to evolve for sulfatase activity than for phosphatase activity, which perhaps explains the prevalence of phosphate over sulfate esters in biology. Despite this, however, it is the same multitude of potential pathways that makes phosphate esters so versatile to catalyze also so difficult to study, and there are a large number of open questions remaining in the field, which need urgent addressing in light of the biological importance of phosphates.…”
Section: Why Nature Really Used Phosphatementioning
confidence: 99%
“…Catalytic proficiencies range from K tx À1 = 10 4.6 m À1 to K tx À1 = 10 8.6 m À1 , and so the transition states of the reactions they catalyze are bound more strongly than the substrates (K M À1 = 10 3.5AE1.0 m À1 ). [13,30] Natures enzymes, on the other hand, exert massive [8,34] Naturally, the catalytic efficiency (k cat /K M ) of such enzymes is often limited only by the diffusion rate of the substrate and ranges from 10 4 to 10 9 m À1 s À1 . In comparison, catalytic antibodies fall short of this limit by 4 orders of magnitude or more (k cat /K M = 10 2 -10 5 m À1 s À1 ).…”
Section: Catalytic Antibodiesmentioning
confidence: 99%
“…[6] Remarkably, K tx À1 spans 21 orders of magnitude (10 8 to 10 29 m À1 ) [6,8] for enzymes that have been studied to date, [6,[9][10][11][12] with an average K tx À1 value of 10 16.0AE4.0 m À1 . [13] This value corresponds to an average DG value for transition-state binding of 22 kcal mol À1 , but can range up to 38 kcal mol À1 , much higher than a noncovalent TS binding free energy of 15 kcal mol À1 .…”
Section: Introductionmentioning
confidence: 99%
“…Entretanto, a literatura ainda aponta outras perspectivas sobre o vasto poder catalitico das enzimas, podendo alcançar, por exemplo, velocidades de reação aproximadamente 10 10 a 10 26 vezes superiores aos encontrados na ausência do catalisador. 8 Diferente dos catalisadores metálicos nos processos químicos, as enzimas agem como um reagente ambientalmente favorável, uma vez que são completamente degradáveis e os processos enzimáticos são realizados sob condições operacionais mais brandas. Ainda, as reações biocatalíticas podem transformar uma grande variedade de substâncias naturais ou não, em ambiente aquoso ou orgânico.…”
Section: Introductionunclassified